Evaluasi Kebijakan Program Jaminan Kesehatan Daerah (JAMKESDA) di Kabupaten Semarang Tahun 2015 - Destya Kusuma Dewi; Kushandajani .; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2017)
EVALUATION OF PROGRAM JAMKESDA IN SEMARANG REGENCY 2015ABSTRACTHealth is a fundamental right of everyone and every citizen desire to get health service. When doing daily activity, every people are need healthy body. For some peoples, health is so expensive, even there’s a quote said “orang miskin dilarang sakit”. Why that prespective could be happened, because of the topic that has revealed lately is about how difficult for poor peoples to get their good health service from the government. This thing happened because of economic problems, because poor peoples can’t pay the medical threatment that they should be pay.But, as that prespective, it doesn’t mean that the government is quiet. Especially the government of Semarang Regency has released a policy JAMKESDA (The Guarantee of Regional Health) in Semarang Regency that ruled in Perbup No. 7 in 2015 to give a help in health service for poor peoples. That’s why, to know the effectivity of this policy, the writer is formulates the problem of this research to “What effect from JAMKESDA program for civil society in Semarang Regency?”This research has a purpose to describe the implementation process of JAMKESDA program in Semarang Regency, and also to figure out the impact from that program. Type of this research is descriptive research. The primary source of this research is from inerviews with the informants used purposive sampling technique. The data analysis technique is by used data reduction, served and took the conclusion.From this research, the result is known that JAMKESDA policy was helped poor peoples for get financing assistance for health service. This policy shown the satisfaction of civil society whom have a low economic. Suggestion from the writer is the budget of JAMKESDA program that still in less is need to be add, in case the price of health needs is keep increasing every year. So that this increase can covers the health needs from all of poor peoples in Semarang Regency.Keyword: Health, JAMKESDA program, Semarang Regency